2016
DOI: 10.1002/ajh.24492
|View full text |Cite
|
Sign up to set email alerts
|

Early event status informs subsequent outcome in newly diagnosed follicular lymphoma

Abstract: Recent advances in follicular lymphoma (FL) have resulted in prolongation of overall survival (OS). Here assessed if early events as defined by event-free survival (EFS) at 12 and 24 months from diagnosis (EFS12/EFS24) can inform subsequent OS in FL. 920 newly diagnosed grade 1–3a FL patients enrolled on the University of Iowa/Mayo Clinic Lymphoma SPORE Molecular Epidemiology Resource (MER) from 2002–2012 were initially evaluated. EFS was defined as time from diagnosis to progression, relapse, re-treatment, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
162
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 200 publications
(174 citation statements)
references
References 26 publications
8
162
0
4
Order By: Relevance
“…Our analysis of the National LymphoCare Study identified the poor prognostic impact of POD24, with 50% OS at 5 years, compared to 90% in patients without early progression (Casulo et al , ). These findings have had high reproducibility and validity in a number of studies and, as such, POD24 is considered among the most robust markers of poor outcome in FL (Jurinovic et al , ; Maurer et al , ). Earlier time points of progression have also been evaluated by Maurer and colleagues.…”
Section: Diagnosis and Disease Assessmentmentioning
confidence: 98%
“…Our analysis of the National LymphoCare Study identified the poor prognostic impact of POD24, with 50% OS at 5 years, compared to 90% in patients without early progression (Casulo et al , ). These findings have had high reproducibility and validity in a number of studies and, as such, POD24 is considered among the most robust markers of poor outcome in FL (Jurinovic et al , ; Maurer et al , ). Earlier time points of progression have also been evaluated by Maurer and colleagues.…”
Section: Diagnosis and Disease Assessmentmentioning
confidence: 98%
“…Early progression, most commonly defined as progression within 2 years after starting rituximabchemotherapy, occurs in ;20% of patients and has recently been associated with poor outcome. [6][7][8][9] Similarly, transformation to aggressive lymphoma, occurring in 2% to 3% of patients per year, has repeatedly been linked to adverse prognosis when compared with patients not experiencing transformation. [10][11][12][13][14][15] There is an association between early progression and transformation.…”
Section: Medscape Continuing Medical Education Onlinementioning
confidence: 99%
“…Although it is unclear whether there is a late plateau in the HT curves [9]; HT is more frequent [7,8] and aggressive [10,11] shortly after diagnosis. Conversely, patients with remission persisting 2 years after diagnosis (or perhaps as early as 1 year) can expect to live as long as the general population [12], which seems to indicate that their risk of death from either the disease or toxicity is lower. In a recent study analyzing the outcome of FL patients based on their response to front-line ICT [7], we found that most patients with ICT-refractory disease were dead at the time of analysis (31/53, 58%), mostly due to lymphoma (27/31, 87%) while only a minority of ICT-sensitive patients had died (35/290, 12%), 14 (40%) due to lymphoma and 10 (29%) due to toxicity (unpublished data).…”
Section: Letter To the Editormentioning
confidence: 99%